CMOS Readout Chips for Implantable Multimodal Smart Biosensors - Nawito, Moustafa (Springer Fachmedien Wiesbaden : Vieweg, 2018)
Moustafa Nawito describes in detail the development process of a novel platform of Readout Integrated Circuits (ROICs), which enable the realization of miniaturized multi-parameter biomedical implants intended for long-term in-vivo monitoring. He presents new circuits and techniques for fully integrated sinusoidal generation, electrochemical impedance spectroscopy as well as on-chip measurement of pH levels, oxygen concentration and temperature. The author draws conclusions of the development process and delivers guidelines for further innovations. Content The SMARTImplant Project Cyclic ADC with Offset Subtraction New Sine-Wave Generation Method New Synchronous Impedance Spectroscopy Method On-Chip Temperature Measurement Ultra-Thin Chip Considerations Target Groups Lecturers, students and practitioners in the field of Electrical Engineering, Electronics, Medical Technology and Biotechnology The Author Moustafa Nawito is a mixed-signal electronic chip designer at the Institut für Mikroelektronik Stuttgart (IMS CHIPS) with focus on analog circuits. His research interests include analog to digital converters, on-chip signal generation and biomedical applications.